Targeting soil acidity investments at scale in Kenya - Gebrekidan, Bisrat Gebrekidan; Chamberlin, Jordan; Madaga, Lavinia; Silva, João Vasco (CIMMYT, 2025)
Soil acidity is a long-recognized one of the many constraints to agricultural production in Kenya and has motivated extensive agronomic research on crop and soil responses to liming. However, the use of agricultural lime remains limited on smallholder farms, even in areas where soil acidity is severe. High lime costs are frequently cited as a barrier to adoption, yet most targeting efforts continue to rely primarily on soil property maps without explicit consideration of the economic returns to liming investments at the farm scale. In this paper, we apply a spatially explicit ex ante targeting framework that integrates soil acidity indicators, crop response modelling, spatial variation in input and output prices, and heterogeneity in farm productivity to assess the economic viability of liming across Kenya. Using high resolution spatial data, we generate location specific estimates of acidity related yield losses, lime requirements, and both short run and multi-year economic returns to remediation. Our results show that while soil acidity is widespread in Kenya’s major agricultural regions, economically viable opportunities for liming are far more spatially concentrated. Predicted agronomic yield responses occur across large areas, but positive economic returns emerge only under specific combinations of lime requirements, baseline productivity, and price conditions. Returns also vary substantially within locations across farms and initial productivity levels. These findings highlight the importance of integrating biophysical and economic information to guide the design and targeting of soil acidity interventions in Kenya.